Jane Grey Swisshelm : An Unconventional Life, 1815-1884 - Hoffert, Sylvia D. (Book collections on Project MUSE., 2004)
19th-century newspaper editor Jane Grey Swisshelm (1815-1884) was an unconventionally ambitious woman. While she struggled in private to be a dutiful daughter, wife, and mother; she publicly critiqued and successfully challenged gender conventions that restricted her personal behavior and limited her political and economic opportunities.